REFORMULATION OF ADMINISTRATIVE SANCTIONS AGAINST PPAT FOR NEGLIGENCE IN REQUESTING PROOF OF BPHTB PAYMENT - Syakir Prayoga; Shinta Hadiyantina; Arini Jauharoh (Universitas Nurul Jadid, 2025)
This study aims to examine the reformulation of administrative sanctions imposed on the Land Deed Official (PPAT) who neglects to request proof of payment for the Land and Building Acquisition Duty (BPHTB) before signing the deed of land transfer. As a public official authorized to create authentic deeds, PPAT is responsible for ensuring the completeness of administrative requirements related to BPHTB. However, the administrative fine of IDR 10,000,000 for a PPAT’s negligence is deemed disproportionate, considering the amount of honorarium received by the PPAT based on the applicable regulations. Based on a literature review and interviews with PPAT in Malang Regency, this study highlights the injustice of imposing sanctions on PPAT, which essentially only fulfills administrative obligations in the preparation of the deed of land transfer. Meanwhile, the obligation to pay BPHTB lies with the taxpayer. This study offers a reformulation of administrative sanctions that is fairer by considering the PPAT’s authority, in line with the principles of legal justice. It is hoped that the findings of this study will contribute to the improvement of regulations related to taxation and land registration in Indonesia. Reformulation, Administrative Sanctions, PPAT, BPHTB Reformulation, Administrative Sanctions, PPAT, BPHTB.